Digital Identification Mexico - World Bank (Washington, DC, 2022)
Authorities in Mexico are seeking solutions to the complex task of improving efficiency in the financial and government sectors when identifying individuals and legal entities, while balancing other public-policy objectives, such as governance, technological neutrality, safety, privacy, and universal coverage. The objective of this document is to describe the identity-management system (IMS) in Mexico and its importance to the financial-sector environment while reflecting on the need for digital identification and authentication procedures and processes. The document will analyze the different options for, and policy implications of, the digital identification of individuals and legal entities in Mexico when meeting financial policy objectives and regulation. This document builds on the principles established by the G20 on digital financial inclusion, the Identity management system analysis, and the common principles on Identification for sustainable development. It takes into account standards and guidelines issued in the financial-sector context that recognize the need to identify individuals and legal entities and intends to provide guidance to Mexican authorities when defining policies that involve the need to identify individuals and legal entities. The document is organized as follows: First, an executive summary presents key observations and recommendations for authorities. A discussion of identification systems in the financial sector comes next, followed by a description of the IMSs in Mexico, including the institutional arrangements, and then by sections on digital identity and the legal framework supporting such infrastructures. Finally, the report concludes with a section on potential actions, which build on initiatives in other countries, which are included along with the report. International standards are attached as appendixes to support the methodology used to elaborate this document.